The Effectiveness of an Anoxic-Oxic-Anoxic-Oxic Sequencing Batch Reactor System (A2/O2-SBR) to Treat Electroplating Wastewater and the Bacterial Community within the System - Tanta Suriyawong; Sasidhorn Buddhawong; Thanit Swasdisevi; Suntud Sirianuntapiboon (Environment and Natural Resources Journal)
This study presents an examination of the effectiveness of an anoxic-oxic-anoxic-oxic sequencing batch reactor (A2/O2-SBR) for treating electroplating wastewater (EPWW). The A2/O2-SBR was monitored for 60 days and the bacterial composition in the treatment system was determined. The system consisted of four reactors, which had the following anoxic/oxic ratios: reactor-I, 0:9 h; reactor-II, 2:7 h; reactor-III, 4.5:4.5 h; and reactor-IV, 7:2 h. The combined cycle time of the reactors was 12 h, the hydraulic retention time (HRT) was five days, and the total volume of mixed liquor suspended solids (MLSS) was 2,000 mg/L. The results demonstrate the importance of an anoxic period for the treatment of heavy metals. Most of the ammonium nitrogen (NH4+-N), Total Kjeldahl nitrogen (TKN), and total nitrogen (TN) were removed during the oxic period. However, as the anoxic period increased, the amounts of TKN, nitrite nitrogen (NO2--N), nitrate nitrogen (NO3--N), and TN declined. Reactor-IV showed a high removal efficiency for heavy metals (Zn2+, 89.74%; Cd2+, 81.37%), TKN (89.20%), and TN (84.25%), and also effectively treated NH4+-N (78.84%), biochemical oxygen demand (BOD5; 93.5%), and chemical oxygen demand (COD; 84.9%). Reactor-IV showed an appropriate difference in the dissolved oxygen (DO) concentration between the anoxic period and oxic period (2.12-2.00 mg/L). The main bacterial phyla in the treatment system were Proteobacteria, Actinobacteria, and Firmicutes, while Pseudomonas vancouverensis and Cryobacterium arcticum were the most common species. The anoxic period and bacterial community have significantly demonstrated the ability to remove Zn2+ and Cd2+ for effective treatment of EPWW.